Association of dietary patterns with general and central obesity among Chinese adults: a longitudinal population-based study - Zhongyi Zhao; Shihan Zhen; Yumeng Yan; Ning Liu; Ding Ding; Juan Kong (BMC Public Health, 2023)
Abstract Background Limited evidence exists for the association between dietary patterns and later obesity phenotypes among Chinese adults. This longitudinal study aimed to evaluate associations of dietary patterns with general and central obesity in Chinese adults. Methods Based on the China Health and Nutrition Survey (CHNS) waves 2004 and 2015, the study was conducted on 4207 adult men and women (age range: 18–65 years). Dietary intakes were assessed by three consecutive 24-h dietary recalls, and dietary patterns were identified using exploratory factor analysis. Longitudinal associations of dietary patterns with general and central obesity were evaluated using logistic regression analyses. Results The prevalence rates of general and central obesity were 14.2% and 42.1%, respectively. Factor analysis extracted three major dietary patterns: “traditional southern,“ “modern,“ and “traditional northern.“ After adjustment for potential confounders, adults in the highest quartile of the traditional southern dietary group were less likely to develop over 10 years general (odds ratio [OR] = 0.50, 95% confidence interval [95%CI]: 0.39, 0.65) and central (OR = 0.52, 95%CI: 0.43, 0.63) obesity compared to those in the lowest quartile group. The modern dietary pattern was not significantly associated with general and central obesity. Adherence to the traditional northern dietary pattern increased the chance of both general and central obesity (OR = 1.61, 95%CI: 1.23, 2.10; OR = 1.64, 95%CI: 1.36, 1.98) after 10 years. Conclusions Our study provides longitudinal evidence for associations between dietary patterns and later obesity phenotypes among Chinese adults. Our findings may guide the development of evidence-based preventive nutrition interventions to control the obesity epidemic.